Paciente masculino de 68 años de edad con hipertensión arterial - Salavarria Jimenez, Linner Natali (2020)
The present clinical case is an adult over 68 years of age, is a teacher, has 2 children and lives in Montalvo, personal pathological history does not refer, allergies and surgical history does not present, within the family pathological background, the mother died of hypertension, he goes to routine control, so he indicates that in recent weeks he has felt bad, with burning eyes, severe headaches and muscle pain; in fear of suffering from hypertension since her mother suffered from that disease; The nutritional assessment is carried out on the patient and his BMI reflects normal weight without cardiovascular risk; the exams corresponding to the patient were performed where they reflected hypercholesterolemia, elevated sodium and decreased potassium; After performing all the exams corresponding to the patient, he is diagnosed with hypertension, so the doctor sends losartan 100mg one a day and is referred to a nutritionist. The individualized nutritional intervention is carried out on the patient, taking into account two aspects, socioeconomic level and their pathological status, a diet that provides the optimal amounts of macro and micronutrients and at the same time covers the patient's caloric requirements, so which prescribes the DASH diet that fits the patient's pathology, is a diet that is used to treat and prevent high blood pressure, it will be divided into 4 meals a day, with a hyposodic characteristic, rich in potassium, normolipid, high in fiber Together with physical activity, the patient's health status will improve. Through the follow-up and monitoring of the patient, positive responses were obtained, his blood pressure stabilized and his cholesterol normalized to almost normal levels.